On the Emergence of Anthropogenic Signal in Extreme Precipitation Change Over China. Issue 17 (12th September 2018) - Li, Wei; Jiang, Zhihong; Zhang, Xuebin; Li, Laurent
Abstract: The detection of anthropogenic influences on climate extremes at regional scale is important for the development of national climate change policy. Global climate simulations from phase 5 of the Coupled Model Intercomparison Project under the Representative Concentration Pathway 8.5 scenario are used to examine the time at which an anthropogenic influence becomes detectable in extreme precipitation over China and the change in probability of extreme precipitation with certain magnitudes when the changes are detectable. Anthropogenic influence is not significantly detected over China in the observational record or simulations from 1961 to 2012 based on the test of field significance. Simulations indicate that such change would become detectable in the future by around 2035. Large changes would already manifest by the time of signal detection; for example, extreme precipitation events that occur on average once every 20, 50, and 100 years in current (1986–2005) climate would reduce to about 15, 34, and 63 years on average by the time of detection around 2035. Plain Language Summary: Understanding causes of changes in extreme precipitation can enhance our confidence in future projections of extreme precipitation. The attribution of cause in changes of extreme precipitation is not straightforward at regional scale, due to the presence of strong natural variability in Earth's climate and the lack of long‐term and reliable observational records. This work seeks the anthropogenic signal in extreme precipitation events within the current observational record. It also uses climate models to explore the time at which such a signal would emerge in the future and to assess the associated risks of extreme precipitation events over China. The findings help us to understand the future evolution of Earth's climate and provide useful information for the design and implementation of climate adaptation measures. Key Points: Significant influence of anthropogenic on extreme precipitation events in China has not yet emerged within the observational record (1961‐2012) An anthropogenic signal of changes in extreme precipitation events would be detectable by around 2035 under RCP8.5 scenario Large changes would manifest by the time of signal detection; extreme precipitation events that occur once every 20, 50, and 100 years in the current (1986‐2005) climate will occur once every 15, 34, and 63 years by that time